Non-surgical management of immature maxillary lateral incisor with palato-gingival groove with MTA - Wakia, Tasnim; Islam, Mohammad Aminul; Alam, Md Shamsul (Update Dental College Journal, 2013)
Palato-gingival groove is a developmental anomaly often affecting the maxillary lateral incisor. The aim of this presentation is to describe the clinical management of a maxillary lateral incisor tooth with a palato-gingival groove with perio-endo lesion having immature apex. Despite complex anatomy, this case was managed by using Mineral Trioxide Aggregate plug technique with as a non-surgical endodontic treatment. The tooth was functional without any complication on the basis of regular clinical and radiological evaluation. DOI: http://dx.doi.org/10.3329/updcj.v2i2.15534 Update Dent. Coll. j: 2012; 2 (2): 38-41